Fractional Integral Operators and Their Boundedness on Various Spaces - Hendra Gunawan; Idha Sihwaningrum (Institut Teknologi Bandung, 2007)
This is a survey paper which presents and discusses some results on fractional integral operators and their generalizedversion on both homogeneous and non-homogeneous spaces.